Familial Risk for Exceptional Longevity. Issue 1 (2nd January 2016) - Sebastiani, Paola; Andersen, Stacy L.; McIntosh, Avery I.; Nussbaum, Lisa; Stevenson, Meredith D.; Pierce, Leslie; Xia, Samantha; Salance, Kelly; Perls, Thomas T.
Abstract : One of the most glaring deficiencies in the current assessment of mortality risk is the lack of information concerning the impact of familial longevity. In this article we update estimates of sibling relative risk of living to extreme ages using data from more than 1700 sibships, and we begin to examine the trend for heritability for different birth-year cohorts. We also build a network model that can be used to compute the increased chance for exceptional longevity of a subject, conditional on his or her family history of longevity. The network includes familial longevity from three generations and can be used to understand the effects of paternal and maternal longevity on an individual's chance to live to an extreme age.